Peran Instagram Pada Perubahan Sosial Siswa Di SMA Negeri 1 Simpang Empat (Asahan) - Arif`, Khairul; Kholil, Syukur; Yasmin, Nabila (CV. ITTC INDONESIA, 2023)
The study aims to determine the role of Instagram in the social changes that occur in students at SMA Negeri 1 Simpang Empat (Asahan) in the perspective of New Media Theory and to find out how students minimize the negative impact of using Instagram social media. The study uses a descriptive qualitative research method and new media theory developed by Pierre Levy. Data collection techniques were carried out by interviews, observation and documentation. The results of this this study indicate that Instagram is very closely related to the New Media Theory developed by Pierre Levy because it requires the internet to carry out its functions. Instagram plays a role in changing communication patterns, interaction patterns, habit patterns and information patterns that students do online. The way students minimize the negative impact of using Instagram is by limiting the time they use Instagram, not following accounts that can have a negative impact on students, parcipate in activities outside of school that can support students development and get closer to Allah SWT.